Secondary Myelitis in Dermal Sinus Causing Paraplegia in a Child with Previously Normal Neurological Function - Sakina Rashid; Grace Kinabo; Marissa Kellogg; William P. Howlett; Marieke C. J. Dekker (Case Reports in Neurological Medicine)
Neural tube defects result from failure of neural tube fusion during early embryogenesis, the fourth week after conception. The spectrum of severity is not uniform across the various forms of this congenital anomaly as certain presentations are not compatible with extrauterine life (anencephaly) while, on the other hand, other defects may remain undiagnosed as they are entirely asymptomatic (occult spina bifida). We report a child with previously normal neurological development, a devastating clinical course following superinfection of a subtle spina bifida defect which resulted in a flaccid paralysis below the level of the lesion and permanent neurological deficits following resolution of the acute infection and a back closure surgery.